Employee Performance Assessment Design Based on Spencer Competency and Wage System in "Sumber Pocong" Drinking Water Company - Fitri Agustina (International Journal of Science, Engineering, and Information Technology, 2016)
Bangkalan Perusahaan Daerah Air Minum (PDAM) there are 2 types of employees. Among them are permanent employees and contract employees, employee performance appraisal is still done by using the DP3 system (Daftar Pelaksanaan Penilaian Pekerjaan). While on contract employees there has not been a measured system so that the assessment is done in accordance with the work that has been done. Assessment of contract employees is done by measuring using spencer competence. Selected some criteria that will be used are the spirit of achievement, Proactive, Organizational Awareness, Group Cooperation, Conceptual Thinking, Technical Skills / Professional, Flexible. Used AHP to perform performance appraisal, then do scoring with BARS and calculated wages earned on each employee. The weight value obtained by each criterion is the spirit of achievement has a weight (0.358), proactive criteria have weight (0.182), organizational awareness criteria (0.139) , Criteria for group cooperation (0.113), conceptual thinking criteria (0.085), technical / professional expert criteria have weight (0.057), flexibility criteria have weight (0,038), criteria of commitment to organization has weight (0.027)  Keywords: Performance Assessment, Spencer Competence, Analytical Hierarchy Process, BARS, Wage Calculation